2‐Amino‐5‐iodopyridinium bromide hemihydrate and 2‐amino‐5‐iodopyridinium chloride monohydrate. (5th September 2013) - Polson, Matthew; Turnbull, Mark M.; Wikaira, Jan L.
Abstract : The hydrobromide and hydrochloride salts of 2‐amino‐5‐iodopyridine were prepared from aqueous solutions. The hydrobromide salt, C5 H6 IN2 + ·Br − ·0.5H2 O, crystallizes as a hemihydrate, and exhibits hydrogen bonding and π‐stacking which stabilize the crystal structure. The hydrochloride salt, C5 H6 IN2 + ·Cl − ·H2 O·0.375HCl, crystallized as the hydrate and exhibits similar hydrogen bonding and π‐stacking in the lattice. The most interesting feature of the hydrochloride salt is the presence of an additional fractional HCl molecule which introduces disorder in the location of the water molecule. The additional proton from the fractional HCl molecule is accounted for by the presence of a partial hydronium ion on one of the water sites.